Type IV Laryngotracheoesophageal Cleft Associated with Type III Esophageal Atresia in 1p36 Deletions Containing the RERE Gene: Is There a Causal Role for the Genetic Alteration?. (29th August 2018) - Pelizzo, Gloria; Puglisi, Aurora; Lapi, Maria; Piccione, Maria; Matina, Federico; Busè, Martina; Mura, Giovanni Battista; Re, Giuseppe; Calcaterra, Valeria
Abstract : The causes of embryological developmental anomalies leading to laryngotracheoesophageal clefts (LTECs) are not known, but are proposed to be multifactorial, including genetic and environmental factors. Haploinsufficiency of the RERE gene might contribute to different phenotypes seen in individuals with 1p36 deletions. We describe a neonate of an obese mother, diagnosed with type IV LTEC and type III esophageal atresia (EA), in which a 1p36 deletion including the RERE gene was detected. On the second day of life, a right thoracotomy and extrapleural esophagus atresia repair were attempted. One week later, a right cervical approach was performed to separate the cervical esophagus from the trachea. Three months later, a thoracic termino-terminal anastomosis of the esophagus was performed. An anterior fundoplication was required at 8 months of age due to severe gastroesophageal reflux and failure to thrive. A causal role of 1p36 deletions including the RERE gene in the malformation is proposed. Moreover, additional parental factors must be considered. Future studies are mandatory to elucidate genomic and epigenomic susceptibility factors that underlie these congenital malformations. A multiteam approach is a crucial factor in the successful management of affected patients.